Exosome Encased Spherical Nucleic Acid Gold Nanoparticle Conjugates As Potent MicroRNA Regulation Agents - Alhasan, Ali H. (2013)
Exosomes are a class of naturally occurring nanomaterials that play crucial roles in the protection and transport of endogenous macromolecules, such as microRNA and mRNA, over long distances. Intense effort is underway to exploit the use of exosomes to deliver synthetic therapeutics. Herein, we use transmission electron microscopy to show that when spherical nucleic acid (SNA) constructs are endocytosed into PC-3 prostate cancer cells, a small fraction of them (< 1%) can be naturally sorted into exosomes. The exosome-encased SNAs are secreted into the extracellular environment from which they can be isolated and selectively re-introduced into the cell type from which they were derived. In the context of anti-miR21 experiments, the exosome-encased SNAs knockdown miR-21 target by approximately 50%. Similar knockdown of miR-21 by free SNAs requires a ~3000-fold higher concentration.